Covid-19 and Violence against Women: An Analytical Study in the Context of Bangladesh - Md. Abu Shahen (CV. Literasi Indonesia, 2022)
At the end of 2019, the people of the world experienced the Covid-19 pandemic situation. After a while, the pandemic situation was more acute and threatening to the mass people of the world. Women who have faced violence due to the pandemic situation. However, this paper tried to explore the relationship between Covid-19 and violence against women in the context of Bangladesh. This paper is quite qualitative in manner, and reports, articles, and content on relevant issues have been used as the sources of data. Simultaneously, the study found that the rate of VAW during Covid-19 has increased where women are passing a miserable conditions due to the pandemic situation both in the home and outside of the home. In most cases, women are beaten by their intimate partners and forced to go to the parental house. The Paper also found some reasons for increasing those violent occurrences such as mental depression, economic hardship, wife’s excessive demands, children disturbance, and male-dominant attitudes and behaviors. Moreover, it is inevitable to take collaborative initiatives where the government will take lead and non-government organizations and mass people will play a supportive role to eliminate violence against women during the pandemic situations.